2016
DOI: 10.1093/alcalc/agw009
|View full text |Cite
|
Sign up to set email alerts
|

Relative Role of Akt, ERK and CREB in Alcohol-Induced Microglia P2X4R Receptor Expression

Abstract: These findings provide important clues to the underlying mechanism of purinoceptors in alcohol-induced microglia immune suppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 44 publications
(61 reference statements)
1
20
0
Order By: Relevance
“…It is also known that in more drastic cases, alcohol can even induce apoptosis in microglia [72] . Many of these effects can be attributed to the alcohol-induced expression of P2X4 in microglial cells, and involve the inhibition of the AKT and ERK cascades [73] . This increase in P2X4 is observed at both mRNA and protein levels [71] .…”
Section: Functional Roles Of P2x4 In the Nervous Systemmentioning
confidence: 99%
“…It is also known that in more drastic cases, alcohol can even induce apoptosis in microglia [72] . Many of these effects can be attributed to the alcohol-induced expression of P2X4 in microglial cells, and involve the inhibition of the AKT and ERK cascades [73] . This increase in P2X4 is observed at both mRNA and protein levels [71] .…”
Section: Functional Roles Of P2x4 In the Nervous Systemmentioning
confidence: 99%
“…It is now known that mutant p53 proteins not only lost their transcriptional function (loss of function), but also commonly obtain new function (gain of function). 7 For instance, p53-R175H exhibits a gain of oncogenic function in driving cell migration and invasion. 4 , 8 Studies from animal models have confirmed that mice bearing a mutant p53 allele show more aggressive and metastatic tumor than p53 null.…”
mentioning
confidence: 99%
“…137 Supporting evidences indicate that P2X4 receptors physically couple with GABA A receptors as well as with the P2X 2 receptors and this cross talk may play a role in regulating synaptic signaling and plasticity of neurons. 160 Alcohol abuse is known to enhance neuroinflammation through P2X 4 Rs activation 161 and there are suggestions of implication of P2X 4 Rs in tolerance to morphine and hyperalgesia induction by morphine. 161,162 P2X 4 receptors are upregulated in TBI 6 , in acute experimental encephalomyelitis (EAE) rodent model of multiple sclerosis 17 and following hypoxia and ischemia events.…”
Section: P2x 4 Receptor and Functions In The Cnsmentioning
confidence: 99%
“…160 Alcohol abuse is known to enhance neuroinflammation through P2X 4 Rs activation 161 and there are suggestions of implication of P2X 4 Rs in tolerance to morphine and hyperalgesia induction by morphine. 161,162 P2X 4 receptors are upregulated in TBI 6 , in acute experimental encephalomyelitis (EAE) rodent model of multiple sclerosis 17 and following hypoxia and ischemia events. 163 In neurons, P2X 4 R has shown to stimulate activation of the inflammasome caspase-1 resulting in cytokines IL-18 and IL-b release, and in P2X 4 R knockout mice, impaired inflammasome signaling was reported to couple to the reduction of IL-b level.…”
Section: P2x 4 Receptor and Functions In The Cnsmentioning
confidence: 99%